2006
DOI: 10.1021/bi061551q
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of Escherichia coli MoeA:  Two Functional Activities Map to the Active Site Cleft,

Abstract: SUMMARYThe molybdenum cofactor is ubiquitous in nature, and the pathway for Moco biosynthesis is conserved in all three domains of life. Recent work has helped to illuminate one of the most enigmatic steps in Moco biosynthesis, that of metal ligation to molybdopterin (the organic component of the cofactor) to form active cofactor. In Escherichia coli, the MoeA protein mediates Mo ligation to molybdopterin while the MogA protein enhances this process in an ATP-dependent manner. The xray crystal structures for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…The missing C6 cassette forms large parts of subdomain 2 (Fig. 8B), which forms the upper half of the GephE active site harboring residues important for Moco biosynthesis as shown for the homologous Cnx1 protein (40) as well as MoeA (41). The fact that Geph2 is expressed at similar levels as other variants (including blob formation) points to an overall maintenance of the structural integrity of GephE.…”
Section: Discussionmentioning
confidence: 82%
“…The missing C6 cassette forms large parts of subdomain 2 (Fig. 8B), which forms the upper half of the GephE active site harboring residues important for Moco biosynthesis as shown for the homologous Cnx1 protein (40) as well as MoeA (41). The fact that Geph2 is expressed at similar levels as other variants (including blob formation) points to an overall maintenance of the structural integrity of GephE.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, given the known transfer and binding of MPT-AMP in the E domain, MPT-AMP was modelled into the proposed active site of the E domains ( Figure 7B, yellow subunit), which is surrounded by functionally important residues [44]. Crystal structures of gephyrin E domain [39] and E. coli MoeA [44] disclosed that subdomain 1 is highly mobile and hosts additional active-site residues [44]. In our model, those residues face the G-domain-bound MPT-AMP in a conformation that we call a 'closed' state ( Figure 7C, orange and yellow subunits).…”
Section: Crystal Structure Modelling Supports Product-substrate Channmentioning
confidence: 99%
“…Moco is almost ubiquitous in nature, and its biosynthesis, which comprises several steps, is highly conserved (73). In bacteria, such as E. coli, MoeA is required in the final step of Moco biosynthesis for the mononuclear Mo is attached to MPT, and it is enhanced by MogA (58,72). In this study an moeA-homologous gene was insertionally inactivated in several of the MS-negative mutants of strain B4.…”
Section: Degradation Of Ms Has Been Previously Investigated In Onlymentioning
confidence: 99%
“…On the other hand, in most bacterial Modependent enzymes, the fusion of a nucleotide monophosphate to the Moco side chain is required. This reaction is catalyzed by MobA, yielding the molybdopterin guanine dinucleotide (MGD) cofactor, which is the active cofactor of most prokaryotic molybdoenzymes (50,58) and is also found in enzymes belonging to the DMSOR family. In this study, a gene coding for a homologue of the MGD biosynthesis protein (MobA) was identified and located adjacent to moeA in the V. paradoxus strain B4 genome.…”
Section: Degradation Of Ms Has Been Previously Investigated In Onlymentioning
confidence: 99%